Fostering knowledge sharing: Design principles for persuasive digital technologies in open innovation projects - Max Jalowski; Sascha Julian Oks; Kathrin M. Möslein (Creativity and Innovation Management, 2022)
Integrating knowledge is crucial for open innovation, and digital technologies can play a central role because they support knowledge sharing. In open innovation projects, in particular, little is known about the role of technology. Here, the individual behaviour of users is taken into account concerning the extent to which knowledge is shared. Therefore, persuasive technologies offer the potential to foster sharing. In particular, to facilitate the construction of future digital technologies, this study applies a design science research approach to create and analyse artefacts as a research contribution and develop design principles as a step towards a nascent design theory. We present insights from the design and application of three artefacts in different stages of open innovation processes. Results show that digital technologies can be used for various purposes: to build a common understanding, support design phases, communicate ideas and simplify the application of the technology for the user. Our research provides insights into the role of digital technologies for knowledge sharing in open innovation projects, and four design principles are found to facilitate the construction of future persuasive digital technologies for open innovation projects.
Keywords: 330; design principles; design science research; digital technologies; knowledge sharing; open innovation; persuasive technology